Phonological Wordplay in the Dad Jokes YouTube Channel - Amalia Nafianty Shagita; Abd Hannan EF; Dedi Sulaeman (Journal of English Language and Education, 2026)
Humor in spoken interaction often relies on phonological manipulation to create ambiguity and generate comedic effects. This study aims to analyze the types of wordplay found in the Dad Jokes YouTube channel and to examine how sound-based manipulation contributes to humor creation in spoken interaction. The data were analyzed using Dirk Delabastita’s theory of wordplay, which includes homonymy, homophony, homography, and paronymy. This study employed a qualitative descriptive method by identifying jokes containing wordplay from selected videos in the Celebrity Dad Jokes playlist. The findings showed that paronymy was the most dominant type, occurring in 62 out of 120 identified data, followed by homonymy (30 data), homophony (27 data), and homography (1 datum). The results also demonstrated that prosodic features, particularly pauses and intonation, contributed to humor creation by triggering ambiguity, reinterpretation, and surprise through wordplay. The study concludes that phonological features play a significant role in shaping humor in spoken dad jokes on YouTube.